(untitled) (Resv, 2021)
This article discusses from a semiotic perspective the results of the Special Reportpublished by the Instituto de Estudios Peruanos in 2019 on Peruvianness and the Bicentenary. The theoretical premise underlying the discussion conceives of national identities not as essential or pre-social, but as articulated sets of discourses, imaginaries and narratives, amongst multiple other signifying elements, which allow individuals to attribute meaning to social reality in terms of a national belonging. By analyzing a selection of the results presented in the Special Report, the article aims at throwing some light on the discursive and imaginary basis of national identity as it is perceived by Peruvians, two hundred years after the Independence.